Relationship of counselling self-efficacy, job satisfaction and organizational commitment among malaysian school counsellors - Ooi, Pei Boon (2016)
The roles of school counsellors have evolved over the years and the professional and personal development of the school counsellors receives scarce attention from researchers, policy makers and authorities. Past research studied on the relationship of the counselling self-efficacy, job satisfaction and the organizational commitment was not in the context of Malaysian counsellors. Thus, this study was conducted to study the relationship of the counselling self-efficacy, job satisfaction and the organizational commitment among school counsellors in Malaysia. The descriptive and correlational research design was used. The sample size was 541 secondary school counsellors selected via the simple random sampling method from all over Malaysia. A structured questionnaire which comprised of 5 different inventories was used, (a) sources of counselling selfefficacy, (b) perceived access to training and perceived supervisor support towards training, (c) Minnesota Satisfaction Questionnaire, (d) Counselling Self-Estimate Inventory (COSE), and (e) Three-Component Model (TCM) Employee Commitment Survey. The Structural Equation Modelling (SEM) was used to determine the model fit of the proposed models, and the direct and indirect effects of the mediator. The findings indicated that the correlation between the variables studied (mastery experience, social persuasion, vicarious learning, access to training, and perceived supervisor support towards training) and counselling selfefficacy were significant and as predicted. Mastery experience reported the strongest relationship with counselling self-efficacy, followed by social persuasion and vicarious learning. Both environmental determinants reported moderate correlation with counselling self-efficacy. Counselling self-efficacy was positively related to job satisfaction, and job satisfaction was also positively related to the organizational commitment of the school counsellors. The Bootstrapping procedure also revealed that counselling self-efficacy emerged as significant partial mediator to only: (a) mastery experience and job satisfaction and (b) perceived supervisor support towards training and job satisfaction. The finding revealed that mastery experience, perceived supervisor support towards training and counselling self-efficacy contributed 20% variance in job satisfaction among school counsellor. The findings could be used to further enhance counselling self-efficacy and job satisfaction of the school counsellors. Counsellor educators could focus on the professional and personal development of the school counsellors through structural opportunities for efficacy-building on mastery experience, cultivating sense of belief in performing counselling tasks, and obtaining the supervisors’ support towards training.